SUICIDE ATTEMPTS AMOMG WOMEN DEPRIVED OF THEIR FREEDOM IN A PRISON UNIT - Mariana Farias; Mariluci Alves Maftum; Manuela Kaled; Aline Cristina Zerwes Ferreira; Rafael Haeffner; Fernanda Carolina Capistrano; Lillian Andressa Zanchettin (Universidade Federal do Paraná, 2024)
Objective: to describe the occurrences and factors associated with attempted suicide among women deprived of their freedom in a prison unit. Method: a cross-sectional study conducted at a detention facility in Paraná - Brazil, with 30 women, with data collected in 2022 using the Columbia-Suicide Severity Rating Scale instrument and another one prepared by the authors and analyzed descriptively and inferentially. Results: during their lifetime, 16 (53.3%) women presented suicidal behavior; 14 (46.7%) made actual suicide attempts; 14 (46.7%) had physical damage; and 10 (33.3%) preparatory acts. An actual suicide attempt was associated with suicidal thoughts before arrest (p<0.01) and with thoughts during arrest (p<0.02). Conclusion: previous history of ideation influenced the suicide attempt. Therefore, it is important to evaluate suicidal behavior in the admission and permanence of women deprived of their freedom. This study contributes to reducing the gap in the Brazilian scientific production on this topic with this population segment.